The Dichotomous Responses Driven by β-Defensins - Shelley, Jennifer R.; Davidson, Donald J.; Dorin, Julia R. (Frontiers in Immunology, 2020)
Defensins are short, rapidly evolving, cationic antimicrobial host defence peptides with a repertoire of functions, still incompletely realised, that extends beyond direct microbial killing. They are released or secreted at epithelial surfaces, and in some cases, from immune cells in response to infection and inflammation. Defensins have been described as endogenous alarmins, alerting the body to danger and responding to inflammatory signals by promoting both local innate and adaptive systemic immune responses. However, there is now increasing evidence that they exert variable control on the response to danger; creating a dichotomous response that can suppress inflammation in some circumstances but exacerbate the response to danger and damage in others and, at higher levels, lead to a cytotoxic effect. Focussing in this review on human β-defensins, we discuss the evidence for their functions as proinflammatory, immune activators amplifying the response to infection or damage signals and/or as mediators of resolution of damage, contributing to a return to homeostasis. Finally, we consider their involvement in the development of autoimmune diseases.